Pharmacological approach for treatment of influenza - Simova, Milica; Serafimovska, Tijana; Trajkov, Dejan; Darkovska Serafimovska, Marija (INSTITUTE OF KNOWLEDGE MANAGEMENT SKOPJE, 2021)
Influenza is a viral disease which happens most often in the autumn and winter months. The most common symptoms that occur are fever, cold, sore throat, muscle aches, headaches, cough, weakness, and lethargy. There are several types of influenza viruses (A, B and C), of which the most common type in human are A (H1N1) and type B viruses. Influenza virus belongs to the group of enveloped viruses - it has a coating that originates from the membrane of the host cell that the virus carries with it when it leaves the cell. Hemagglutinin and neuraminidase are the two main types of glycoproteins present in the outer shell of influenza viruses. The M2 protein, which is a transmembrane channel present in the virus shell, passes through the lipid layer. Immediately below the lipid sheath is another protein called the matrix protein, or M1, which is positioned to enclose the nucleus of the virion on all sides. Inside the central nucleus of the virion are a non-structural protein and a ribonucleoprotein complex (RNP). The RNP complex consists of 8 gene segments of varying lengths, while the RNA-dependent RNA polymerase is a heterotrimer consisting of 2 polymerase bases (PB1 and PB2) and one polymerase acid subunit. All these sites are target sites for influenza medications. Methods for treatment to influenza vary depending on the severity of the disease. There are several approved medications for therapy of influenza available on the market. Neuraminidase inhibitors (oseltamivir, zanamir) are the most used medicines. To overcome the limitations of these medicines (due to rapid mutations and resistance of the virus to neuraminidase inhibitors), several attempts have been made to develop new medicines against the influenza virus. Some of them are already approved (baloxavir approved in 2018 in Japan and the United States and favipiravir - nucleoside analogue which after oral ingestion is phosphoribosylated intracellularly to be transformed into an active form) or are in an advanced (second) stage of development (pimodivir which inhibits viral replication and monoclonal antibodies). Oseltamivir due to its ease way of administration (perorally) remains the medicine of choice for the treatment of influenza. However, although neuraminidase inhibitors (especially oseltamivir) remain the medicine of choice for influenza treatment, their overuse should be avoided. Accurate selection of patients who really need this treatment is necessary. There are a number of preventive measures we can take to protect ourselves from this virus and to prevent its spread. But, vaccines remain the best option for reducing the number of infections and complications that can occur from the influenza virus.
Keywords: influenza; antiviral drugs; vaccines